2016
DOI: 10.1103/physrevb.94.205411
|View full text |Cite
|
Sign up to set email alerts
|

Changes in work function due to NO2 adsorption on monolayer and bilayer epitaxial graphene on SiC(0001)

Abstract: The electronic properties of monolayer graphene grown epitaxially on SiC(0001) are known to be highly sensitive to the presence of NO 2 molecules. The presence of small areas of bilayer graphene, on the other hand, considerably reduces the overall sensitivity of the surface. We investigate how NO 2 molecules interact with monolayer and bilayer graphene, both free-standing and on a SiC(0001) substrate. We show that it is necessary to explicitly include the effect of the substrate in order to reproduce the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…measured by KPFM was 135.9 meV lower than the WF of a BLG [51]. Later studies reported the same results [10,37,38,43,44,52] and indicated that the SLG could be chemically less stable than the BLG and FLG [53]. Panchal et al studied the surface potential and the WF of the SLG and BLG domains via a combination of electrical functional microscopy and spectroscopy techniques [54].…”
Section: Thickness Dependence Of the Graphene Work Functionmentioning
confidence: 91%
See 1 more Smart Citation
“…measured by KPFM was 135.9 meV lower than the WF of a BLG [51]. Later studies reported the same results [10,37,38,43,44,52] and indicated that the SLG could be chemically less stable than the BLG and FLG [53]. Panchal et al studied the surface potential and the WF of the SLG and BLG domains via a combination of electrical functional microscopy and spectroscopy techniques [54].…”
Section: Thickness Dependence Of the Graphene Work Functionmentioning
confidence: 91%
“…Upon contact of graphene with a metal (insulator), the WF difference results in transfer of the charge to create an interface dipole moment, which controls the WF of a graphene layer [9,50,52]. The dipole size and the sign and magnitude of doping in a graphene layer depend on the type, thickness, and WF of the contact.…”
Section: Effect Of the Type Of Graphene Contact On Its Work Function ...mentioning
confidence: 99%
“…It is worth noting that the work function after NO 2 adsorption increases by 0.46 eV, which is even larger than what has been reported for graphene. 58 …”
Section: Resultsmentioning
confidence: 99%
“…The Fe3O4 NP DEG sensor was not tested with CO. To NO2, the Fe3O4 NL DEG sensor exhibited the highest and the untreated PEG sensor the second highest response. The strong gas response towards NO2 with PEG could be due to the fact that NO2 sensing is highly dependent on the substrate and has a known high binding energy with EG [136]. The Fe3O4 NP DEG sensor (not shown in Table 6) exhibited one of the lowest responses of all sensors, which can partly be explained with the lower exposure time (see section 4.3.1 for influence of exposure time on response magnitude).…”
Section: Gas Measurementsmentioning
confidence: 98%